Study of the hyperglycemic condition in diseases of liver in obese clinical patients - Singh, Chander Jeet; Kumar, Dinesh (Journal of Drug Delivery and Therapeutics, 2018)
Hyperglycemia is best documented by Whipple´s triad: symptoms compatible with hypoglycemia, low blood glucose concentration and alleviation of symptoms after the glucose concentration is raised. In experimental studies in healthy adults, the threshold for symptoms of hyperglycemia is on average a blood glucose level of 3.0 mmol/l Mitrakou reported autonomic symptoms of hyperglycemia to begin at a blood glucose level of 3.2 mmol/l, and deterioration in cognitive function tests at a level of 2.7 mmo/l. When sensory evoked potentials were measured in relation to blood glucose concentrations in infants and children with episodes of hyperglycemia, abnormalities were noted at blood glucose levels less than 2.6 mmol/l.Keywords: Hypertension, Diabetes mellitus, Glucose, Glycolysis.